CONCEPTUAL REVIEW ON RELIGIOSITY, WORK-LIFE BALANCE (WLB) AND EMPLOYEE PERFORMANCE IN THE HIGHER EDUCATION INSTITUTIONS (HEIs) - Kumarasamy, Mokana A/P Muthu; Hasbolah, Farhana; Hamzah, Hanissah; Fazmi, Khairun Natasha Mohd; Omar, Siti Aisyah; Bhuiyan, Abul Bashar (American International Journal of Social Science Research, 2021)
Working from home (WFH) is now becoming a new normal, and today it brings a big change in the way people think and act. However, some people find that working from home is a big challenge, especially for those with families and young children. This is not easy and it leads to stress and burdens because the employees were not able to share a good time with their family and work demands. This study aims to identify the influencing factors of Work-life balance (WLB) on employee performance and moderating effect of religiosity towards WLB and employee performance of HEIs. The study will be used to accumulate empirical literature by the name of religiosity towards WLB and employee performance in different online database sources. The review findings show that there is a significant effect of WLB especially, technological, institutional, and individual factors are considered the most influential effects on employee performance. This study also identified that there is a moderating effect of religiosity towards WLB and employee performance of HEIs. The findings will be used to develop a reach framework and will be conducted a rigorous depth study and will be drawn policy guidelines for further improvement of WLB and employee performance in HEIs.